Synthesis and Evaluation of Important Biologically Active Heterocyclic Compounds: Schiff Bases, Oxadiazole and Pyrazolyl Derivatives (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
In this work, we prepared an excellent yield of (2-oxo-2H-pyrano[3,2-h] quinolin-4-yl) acetic acid; compound (1) and from the reaction of it with hydrazine hydrate (100%) we obtain 2-(2-oxo-2H-pyrano [3,2-h] quinolin-4-yl) aceto hydrazide (2) which is the starting material for the synthesis of several series of new compounds: such as schiffâ€™s bases (3a-e) and compound (4) in good yields, hydrazide derivatives like compound (5), derivatives of mercapto oxadiazole as compound (6) and derivatives of pyrazolyl as compound (7). All these compounds were found to possess high antimicrobial activity against G+ and G- bacteria and against antifungal as described in scheme (1). Anticancer activity was screened only for compound (1). The IC50 value of it against breast cancer was found = 6.83 ÂµM comparable with that of the drug of doxorubicin which has IC50 = 5.6. As a result these newly compounds from (1) to (7) are considerable as potent compounds for various pharmacological activities.Â